Before Sound: Re-Composing Material, Time, and Bodies in Music - Manca, Tiziano (Bielefeld transcript Verlag, 2023)
In Before Sound, composer Tiziano Manca investigates the premises for and consequences of a major change in his compositional practice: this change emphasizes the temporality of sound and, more recently, the relationship between sounding body and musician. It calls into question the traditional conception of composition and its relation to sound material. Accordingly, Manca examines the theoretical and aesthetic reasons for this shift by interweaving aesthetic reflection on his work with historical research on the notion of musical material and the theory of sound production.
1
Keywords: Writing the Flow: Time, Rhythm and Western Music Notation; Composing; Artistic research; Sound